Surfactant replacement might help recovery of low-compliance lung in severe COVID-19 pneumonia. (August 2020) - Busani, Stefano; Dall'Ara, Lorenzo; Tonelli, Roberto; Clini, Enrico; Munari, Elena; Venturelli, Sophie; Meschiari, Marianna; Guaraldi, Giovanni; Cossarizza, Andrea; Ranieri, V. Marco; Girardis, Massimo
The reviews of this paper are available via the supplemental material section.